2015
DOI: 10.1002/art.39240
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Association of CCR1, KLRC4, IL12A–AS1, STAT4, and ERAP1 With Behçet's Disease in Iranians

Abstract: Objective. To independently replicate the top findings from 4 published genome-wide association studies (GWAS) of susceptibility genes in Behçet's disease (BD).Methods. We tested 14 single-nucleotide polymorphisms (SNPs) in 13 genomic loci (excluding the major histocompatibility complex [MHC], IL10, and IL23R-IL12RB2, which have already been associated with BD in Iranians) for allelic and genotypic associations with BD in 973 patients and 828 controls from Iran and performed meta-analyses of the significantly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 18 publications
3
39
3
Order By: Relevance
“…In addition, the risk hypothetically attributable to the genetic component of the disease was estimated, showing that AA genotype has a large effect on the disease risk. In comparison to other populations [8,10,[16][17][18], in the Italian cohort, the association between rs17482078 and BS susceptibility was weaker. No genotypic correlations, neither 1 3 functional effects were found for the rs27044 G polymorphism in the Italian population.…”
Section: Etiopathogenesiscontrasting
confidence: 74%
“…In addition, the risk hypothetically attributable to the genetic component of the disease was estimated, showing that AA genotype has a large effect on the disease risk. In comparison to other populations [8,10,[16][17][18], in the Italian cohort, the association between rs17482078 and BS susceptibility was weaker. No genotypic correlations, neither 1 3 functional effects were found for the rs27044 G polymorphism in the Italian population.…”
Section: Etiopathogenesiscontrasting
confidence: 74%
“…Individual variants encoding these haplotype tagging SNPs, Met349Val (rs2287987), Asp575Asn (rs10050860) and Arg725Gln (rs17482078), were previously reported recessively associated with Behçet's disease in Turkish3 and Iranian13 studies. Their genotype frequencies were also consistent with recessive association in the Spanish and Chinese populations, but did not reach statistical significance 5 14…”
Section: Discussionmentioning
confidence: 99%
“…Killer cell lectin-like receptor subfamily C, member 4 (KLRC4) is a member of NKG2 receptor family that regulates NK cell function. The association of the KLRC4 gene and BD was first suggested in the GWAS of Turkish and Japanese cohorts [36], and then replicated in the independent study of an Iranian cohort [103].…”
Section: Klrc4mentioning
confidence: 87%
“…The Several SNPs at CCR1-CCR3 locus were associated with BD including rs7616215 in Turkish [40] and rs13084057, rs13092160 and rs13075270 in Chinese Cohorts [102]. In addition, the CCR1 gene was individually associated with BD in multiple cohorts including Turkish, Japanese, and Iranian cohorts [36,103]. Functional studies indicated that CCR1 gene expression in primary human monocytes carrying the BD-risk allele was reduced along with a weaker activity of monocyte chemotaxis [36].…”
Section: Ccr1 and Ccr3mentioning
confidence: 99%